Misconceptions of the Sabbath as Rest: The Social Interpretation of Exodus 23:1-12 and Its Relevance - Jusuf Haries Kelelufna; Sipora Blandina Warella; Brayen Aliong Patty; Dery Anthon Gaszpers; Yohanis Sefwin Noya (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
This article is driven by the many problems related to Sunday activities and land problems in the Moluccas. According to J.H Elliott, the authors analyze the text of Exodus 23:1–12 using the social sciences critique method. Meanwhile, the theory used as an analytical tool is the Structural-Functional theory proposed by Emile Durkheim and Jean Jacques Rousseau’s social contract theory. The results of the analysis are then discussed in relation to the church context in the Moluccas. The study's results found that originally, Sabbath meant to rest within the context of work.